1999
DOI: 10.1021/jo991086l
|View full text |Cite
|
Sign up to set email alerts
|

Highly Stereocontrolled Synthesis of Trifluoromethylated Materials with Allylzincs and Allenylzincs Generated by Umpolung of Palladium Complexes

Abstract: The formation and chemical behaviors of trifluoromethylated allylzinc and allenylzinc reagents derived from the umpolung of allyl- or allenylpalladium complexes have been described. The reactions of these reagents with aldehydes proceeded smoothly to afford highly stereocontrolled γ-(trifluoromethyl)-δ-hydroxy α,β-unsaturated materials. Their configurations determined by the spectral data were anti, and Z-isomers were produced from the system of allylzinc reagents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…Kitazume et al have reported that allylzinc species can generate efficiently from -trifluoromethylated allyl carbonate, and react with various aldehydes in a highly diastereoselective manner (Scheme 49) [117]. Thus, treatment of -trifluoromethylated allyl carbonates 183 with Pd(PPh 3 ) 4 gives the corresponding electrophilic -allylpalladium complex 184, which can react with Et 2 Zn to provide the nucleophilic allylzinc complex 185 in situ, as well as to regenerate Pd(0) species.…”
Section: Transition Metal-catalyzed Allylation or Propargylation Via mentioning
confidence: 99%
“…Kitazume et al have reported that allylzinc species can generate efficiently from -trifluoromethylated allyl carbonate, and react with various aldehydes in a highly diastereoselective manner (Scheme 49) [117]. Thus, treatment of -trifluoromethylated allyl carbonates 183 with Pd(PPh 3 ) 4 gives the corresponding electrophilic -allylpalladium complex 184, which can react with Et 2 Zn to provide the nucleophilic allylzinc complex 185 in situ, as well as to regenerate Pd(0) species.…”
Section: Transition Metal-catalyzed Allylation or Propargylation Via mentioning
confidence: 99%
“…The observed coupling constant between H a and H b of the acetonide 4 a was <1 Hz, as expected for an H ax ,H eq coupling constant in such an acetonide 7. It is also important to note that the anti acetonide with a phenyl group (instead of a 4‐nitrophenyl moiety) has already been prepared by a different approach, and showed a different and typical H ax ,H ax coupling constant of 10 Hz 8…”
Section: Formation Of the Titanium Enolate From 1 And Its Reactivity mentioning
confidence: 99%
“…In our continuous study of stereocontrolled fluorinated materials [12], we would like to describe a practical enzymatic method for a,a-difluoro-b-hydroxy-g,d-unsaturated carbonyl materials with high optical purity in a large scale handling. The absolute configuration of the obtained a,a-difluoro-b-hydroxy-g,d-unsaturated carbonyl materials was determined by the modified Mosher's method with NMR spectral data.…”
Section: Introductionmentioning
confidence: 99%